IMPACT OF PEER PRESSURE ON DIVIDEND POLICY: EVIDENCE FROM FOOD & ALLIED AND POWER & FUEL SECTORS IN BANGLADESH (International Journal of Banking and Finance, 2024)
Firms’ decisions are not independent of their peers. This study aims to assess the impact of peer pressure on firms’ dividend policy. In a sample of 29 firms from 2014–2020, this study employed a fixed effect regression model and revealed that Bangladeshi firms adjusted their dividend policy in response to their peers. Firms adjust the dividend payout ratio (DPR) by 5.6 percent as a response to their peers. Social learning theory, reputation-based model of peer influence, persuasion bias and rivalry-based theory of mimicking explain how peer influence affects a firm’s dividend policy. The findings of positive peer effects on dividend policy are robust to an alternative proxy of dividend policy – dividend yield. Therefore, the study implied that managers’ decisions regarding the dividend policy are not independent of their peer firms. Investors can adjust their expectations of a firm’s dividend policy based on the overall dividend policy in the industry.